Comparison of Selected Quality Parameters of Olive Oils Derived from Conventional and Organic Farming - Dorota Derewiaka; Karolina Majdak; Paulina Pakosz; Beata Drużyńska (Applied Sciences)
This research aimed to qualitatively analyze the composition of selected extra virgin olive oils from organic and conventional farming available on the Polish market. Determination of the fatty acid profile, determination of the sterol content, and measurement of the acidic and peroxide numbers of the olive oils were performed. Moreover, the content of phenolic acids was determined using the HPLC method, and the antioxidant activity was examined using, e.g., the FRAP and DPPH methods, to establish the differences between the analyzed olive oil samples. The most abundant fatty acids in the olive oil were monounsaturated fatty acids (65.60–78.50%) with oleic acid (59.54–75.36%), saturated fatty acids (14.60–20.49%) with palmitic acid (10.93–16.45%), and polyunsaturated fatty acids (7.80–15.04%) with linoleic acid (6.24–14.34%). The phytosterol fraction consisted of β-sitosterol, campesterol, stigmasterol, clerosterol, ∆5-avenasterol, cycloartenol, 24-methylenecycloartenol, and citrostadienol, and its concentration ranged from 775.23 to 1115.70 mg/kg of the olive oils. The conventional method of olive cultivation influenced campesterol concentration in the extra virgin olive oils, and the concentration was higher in such products than in organic. Tests conducted on the reduction of iron ions (FRAP method) showed that the olive oil obtained from conventional farming (except for one product) had slightly higher antioxidant activity (0.23–0.30 μmol TE/g of olive oil) than that obtained from organic farming (0.19–0.26 μmol TE/g of olive oil). The total content of phenolic acids (oleuropein, hydroxytyrosol, and tyrosol) in the extra virgin olive oils ranged from 133.20 to 226.82 mg/kg.